2021
DOI: 10.1590/0037-8682-0536-2020
|View full text |Cite
|
Sign up to set email alerts
|

Electrocardiographic effect of artemisinin-piperaquine, dihydroartemisinin-piperaquine, and artemether-lumefantrine treatment in falciparum malaria patients

Abstract: Introduction: Artemisinin-based combination therapy (ACT), such as artemisinin-piperaquine (AP), dihydroartemisinin-piperaquine (DP), and artemether-lumefantrine (AL), is the first-line treatment for malaria in many malaria-endemic areas. However, we lack a detailed evaluation of the cardiotoxicity of these ACTs. This study aimed to analyze the electrocardiographic effects of these three ACTs in malaria patients. Methods: We analyzed the clinical data of 89 hospitalized patients with falciparum malaria who had… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 35 publications
(32 reference statements)
0
4
0
Order By: Relevance
“…Those ECGs showed that all three regimens had a mild effect on the QT interval. Therefore, they concluded that prolongation of QT interval is seen in all the regimens of malaria, however, this cannot lead to arrhythmias [10].…”
Section: Resultsmentioning
confidence: 99%
“…Those ECGs showed that all three regimens had a mild effect on the QT interval. Therefore, they concluded that prolongation of QT interval is seen in all the regimens of malaria, however, this cannot lead to arrhythmias [10].…”
Section: Resultsmentioning
confidence: 99%
“…Concurrently, more than 80 countries have applied these treatment regimens where most populations have used them for more than a decade already. Moreover, in 2007, in Côte d'Ivoire, the National Malaria Control Programme (NMCP) undertook to assure provision and distribution of ACTs in all malaria treatment centres throughout this state [24][25][26][27][28]. The reasoning behind the use of ACTs is that it is based on the simultaneous rapid elimination of asexual parasitemia, together with the alteration of the sexual stages of gametophytes, subsequently reducing malaria infectivity [29][30][31].…”
Section: Why Fixed-dose Combination Therapymentioning
confidence: 99%
“…Because of a clinically relevant food effect that increases systemic exposure, PQP should be administered in a fasted state to mitigate QTcF prolongation 27,28 . PQP‐induced QTcF prolongation does not appear to translate into an increased risk for torsade de pointes if taken in the fasted state when other QT prolongation risk factors are controlled 29–31 . Conversely, no clinically concerning QTcF prolongation is expected with PYR and there is no clinically relevant food effect with PYR administration 29 .…”
Section: Introductionmentioning
confidence: 99%
“… 27 , 28 PQP‐induced QTcF prolongation does not appear to translate into an increased risk for torsade de pointes if taken in the fasted state when other QT prolongation risk factors are controlled. 29 , 30 , 31 Conversely, no clinically concerning QTcF prolongation is expected with PYR and there is no clinically relevant food effect with PYR administration. 29 Overall, there are no prohibitive overlaps in the PYR and PQP safety/tolerability profiles preventing further evaluation of this combination for malaria chemoprevention.…”
Section: Introductionmentioning
confidence: 99%